Description of a new species of Probrachista (Hymenoptera: Chalcidoidea: Trichogrammatidae) from Ladakh, India - Khan, Mohd Talib; Anis, Shoeba Binte; Zaidi, Nida; Irfan, Mohd; Manhas, Safeer Ahmed (Zootaxa, 2023)
The present paper deals with the description of a new species Probrachista turtukensis Manhas, Anis & Khan sp. nov, from the region of Ladakh, India. A key to world species of the genus Probrachista Viggiani, is also given.